Knowledge about mammography and associated factors: population surveys with female adults and elderly - Ione Jayce Ceola Schneider; Marui Weber Corseuil; Antonio Fernando Boing; Eleonora d'Orsi (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
The purpose of this paper is to describe the knowledge about mammography and to identify associated factors in female adults and elderly. Data were obtained from two population surveys, one with female adults and another with elderly women from Florianópolis (SC) in 2009 - 2010. A descriptive analysis of the variables was carried out, the appropriate mean of responses about mammography was estimated and crude and adjusted Poisson regression was conducted to identify associated factors. Among adults, 23.1% answered all of the questions appropriately and the appropriate average responses was 7.2 (95%CI 7.1 - 7.3) in a total of 9. In the adjusted model, older age, higher education and income were associated with knowledge about mammography. For the elderly, 15.3% answered all questions appropriately and the average of appropriate responses was 6.4 (95%CI 5.2 - 6.5) and the factors associated with knowledge about mammography in the adjusted model were younger age groups, increased education and income, and identification of mammography as the main diagnostic method for breast cancer. Information about mammography can neither be transmitted in a clear way nor be easily understood; there are also demographic and socioeconomic differences concerning the knowledge about the exam.